2008
DOI: 10.1109/vetecs.2008.329
|View full text |Cite
|
Sign up to set email alerts
|

A Wireless Mesh Network-Based Platform for ITS

Abstract: Although efficient and safe transportation of people and goods is paramount transportation problems continue to soar. Traffic congestions are of the most visible of transportation problems in large urban areas. Intelligent Transportation Systems (ITS), exploits and extends information and communication technologies to reverse the deterioration in transportation systems performance. ITS depends, essentially, on gathering and processing real-time traffic information.In this paper, we describe a prototypical proo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The change in time is the individual vehicle travel time, and the space mean speed is calculated as the net time between the scanners divided by the distance. Successful proof-of-concept studies with Bluetooth technology may be found elsewhere (2)(3)(4)(5)(6)(7)(8). As stated previously, one of the strengths of the Bluetooth system is its ability to collect travel times and vehicle speeds anonymously, requiring only a detectable Bluetooth device in the vehicle.…”
mentioning
confidence: 99%
“…The change in time is the individual vehicle travel time, and the space mean speed is calculated as the net time between the scanners divided by the distance. Successful proof-of-concept studies with Bluetooth technology may be found elsewhere (2)(3)(4)(5)(6)(7)(8). As stated previously, one of the strengths of the Bluetooth system is its ability to collect travel times and vehicle speeds anonymously, requiring only a detectable Bluetooth device in the vehicle.…”
mentioning
confidence: 99%
“…Use of a Bluetooth detector and WiFi on a bus is more predictable because the bus users and the passenger-carrying capacity varies so the process of analyzing OD data for each bus stop is very diverse ( 3 5 ). Some approaches combine wireless mesh networks with Bluetooth capabilities by detecting Bluetooth devices attached to cars equipped with wireless networking at specific locations ( 3 , 6 , 7 ) or by the installation of detection equipment at certain locations such as public facilities ( 8 ) or terminals and bus stops. This enables the measurement of travel data and vehicle images ( 9 ) during movement in either direction at a travel node ( 10 ).…”
Section: Related Workmentioning
confidence: 99%
“…Initially, pedestrians were identified by filtering for MAC addresses that could be captured across a distance of 100 meters (Malinovskiy, Saunier, & Wang, 2012). One study detects vehicles using WiFi and Bluetooth devices installed in the car (Ahmed et al, 2008) as well as vehicle detection, with a focus on travel time (Mai et al, 2017). The process captures and reads the MAC address installed on the vehicle and estimates how long it takes from the starting point to the end point using static WiFi placed in several places.…”
Section: Wifi and Non-passenger Data Experimentsmentioning
confidence: 99%